2004
DOI: 10.1182/blood-2003-11-3800
|View full text |Cite
|
Sign up to set email alerts
|

High-dose imatinib mesylate therapy in newly diagnosed Philadelphia chromosome–positive chronic phase chronic myeloid leukemia

Abstract: Imatinib mesylate (STI571) is effective in chronic phase chronic myelogenous leukemia (CML). However, most patients treated with 400 mg imatinib daily have variable levels of residual molecular disease. We treated 114 patients with newly diagnosed chronic phase CML with 400 mg imatinib twice daily. Overall, 109 patients (96%) had a major cytogenetic response (Philadelphia chromosome [Ph] < 35%), and 103 (90%) had a complete response (Ph 0%). With a median follow-up of 15 months, no patient has progressed to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 349 publications
(214 citation statements)
references
References 33 publications
4
206
0
4
Order By: Relevance
“…It was reported that dose intensity was critical to optimize response in CML [23][24][25][26][27] . Based on higher drug exposure in Chinese patients and dose-proportional imatinib exposure [18,19] , a rational conjecture is that Chinese patients would have a better disease response.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that dose intensity was critical to optimize response in CML [23][24][25][26][27] . Based on higher drug exposure in Chinese patients and dose-proportional imatinib exposure [18,19] , a rational conjecture is that Chinese patients would have a better disease response.…”
Section: Discussionmentioning
confidence: 99%
“…42 High-dose imatinib may prevent the development of mutations that confer imatinib resistance. 43 The prognostic impact of BCR-ABL mutations is difficult to determine, and routine mutational analysis is not recommended currently in the absence of treatment failure or suboptimal response. 40,44,45 Suboptimal imatinib response, for instance, may be caused by BCR-ABLindependent factors, such as lack of compliance with long-term therapy.…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
“…In a cohort of 114 newly diagnosed patients who received 800 mg daily imatinib, highdose imatinib was associated with improved rates of CCyR (P ¼ .0005), MMR (P ¼ .00001), and complete molecular response (P ¼ .001) compared with a historic control group that received standard-dose imatinib. 43 A phase 2 dose-escalation study in imatinib-naive patients who were started on 600 mg daily and increased to 800 mg daily if response criteria were not met further demonstrated CCyR and MMR rates that exceeded those of the IRIS trial. 50 These promising results prompted the initiation of several prospective randomized trials evaluating high-dose imatinib in newly diagnosed patients.…”
Section: Imatinib Nilotinib Dasatinibmentioning
confidence: 99%
“…7 However, single-arm, nonrandomized trials have suggested that rates of CCyR and MMR might be improved with a higher initial dose of imatinib. [8][9][10][11] To formally address this question, the Tyrosine Kinase Inhibitor Optimization and Selectivity (TOPS) study randomly assigned 476 patients 2:1 to imatinib 800 or 400 mg daily. At 12 months, there was no statistically significant difference in MMR (46% vs 40%, P ϭ .2035) or CCyR (70% vs 66%, P ϭ .3470), but MMR rates at 3 and 6 months were higher in patients randomly assigned to imatinib 800 mg, as was the CCyR rate at 6 months (57% vs 45%, P ϭ .0146).…”
Section: Imatinibmentioning
confidence: 99%